Immunological reactions to liver-specific membrane lipoprotein (LSP) in experimental autoimmune liver disease in rabbits. - Uibo, R M (1982)
Humoral and cellular immunity to a liver-specific membrane lipoprotein (LSP) was followed in rabbits immunized either with allogenic rabbit LSP (RLSP) or with xenogenic human (HLSP) or bovine (BLSP) antigens. After 4 months of immunization, all rabbits showed histological changes in liver resembling those found in chronic aggressive hepatitis and occasionally also those seen in primary biliary cirrhosis in man. Antibodies reacting to both allogenic as well as xenogenic LSP preparations were found with an enzyme-linked solid phase immunosorbent assay (ELISA) in all immunized rabbits. Lymphocyte transformation tests in unimmunized rabbits showed an occasional response to some of the LSP preparations and a strong response towards an equivalent rabbit kidney preparation (RKSP). After immunization, reactions to LSP preparations increased significantly, while no response to RKSP was observed. The results confirm previous findings and further demonstrate that similar LSP containing preparations from human, bovine and rabbit sources share autoantigenic, liver-specific determinants. In addition, species specific determinants seem to be present in each of the LSP preparations studied.